Revisiting Primary Otoplasty: Surgical Approach to the Prominent Ear. Issue 1 (29th June 2021) - Savetsky, Ira L.; Cohen, Joshua M.; Avashia, Yash J.; Byrd, H. Steve
Abstract : Summary: Prominent ears and other ear deformities are some of the most common congenital deformities of the head, affecting over 10 percent of the general population. In 2018, more than 10, 000 otoplasties were performed in the United States, with over one-third performed on men. The goal of primary otoplasty is creation of a normal-appearing ear without evidence of surgical intervention. This article and video detail the authors' preferred technique for the treatment of prominent ears. This novel method allows for reduction of a hypertrophic concha and obtuse conchoscaphal angle, as well as creation of an adequate antihelical fold.